2007
DOI: 10.1016/j.neuroscience.2007.03.058
|View full text |Cite
|
Sign up to set email alerts
|

The suprachiasmatic nucleus functions beyond circadian rhythm generation

Abstract: We recently discovered that human activity possesses a complex temporal organization characterized by scale-invariant/self-similar fluctuations from seconds to ~4 hour-statistical properties of fluctuations remain the same at different time scales. Here, we show that scale-invariant activity patterns are essentially identical in humans and rats, and exist for up to ~24 hour: six-times longer than previously documented. Theoretically, such scale-invariant patterns can be produced by a neural network of interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
133
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(161 citation statements)
references
References 53 publications
(93 reference statements)
23
133
2
2
Order By: Relevance
“…This is of interest, because scale invariance in activity patterns is found in rodents to be dependent on the SCN (33), and so the changes observed in AD might be taken as indicative of changes occurring in the master clock that are then translated into gross patterns of behavior. This finding is in accordance with the findings from neuropathological studies discussed later.…”
Section: Functional Studies Of Circadian Disruption In Admentioning
confidence: 99%
“…This is of interest, because scale invariance in activity patterns is found in rodents to be dependent on the SCN (33), and so the changes observed in AD might be taken as indicative of changes occurring in the master clock that are then translated into gross patterns of behavior. This finding is in accordance with the findings from neuropathological studies discussed later.…”
Section: Functional Studies Of Circadian Disruption In Admentioning
confidence: 99%
“…Specifically, decreased a (less than 1) in activity fluctuations at large timescales has been observed in animals after the lesion of the SCN (more than approx. 4 h) [7] and in humans with aging and in dementia (more than approx. 2 h) [11].…”
Section: Multiscale Activity Patternsmentioning
confidence: 99%
“…This is consistent with our previous study in which we showed that the SCN itself cannot generate scale-invariant patterns [24] despite the fact that the ). The dashed curve is the fitting line derived from SCN-lesion animals [7]. On the abscissa, n represents the timescale in hours.…”
Section: Scale-invariant Activity Control Requires Normal Circadian Rmentioning
confidence: 99%
“…However, there are examples of neuronal spontaneous electrical oscillations whose function is known, such as neurons from the isolated suprachiasmatic nucleus, which become coupled to perform two main functions, i.e. timekeeping and controlling the circadian overt rhythm (Colwell, 2000;Silver and Schwartz, 2005;Hu et al, 2007;Bernard et al, 2007).…”
Section: Recording From Different Brain Areasmentioning
confidence: 99%